The First Combined Hα and Rest-UV Spectroscopic Probe of Galactic Outflows at High Redshift - Emily Kehoe; Alice E. Shapley; N. M. Förster Schreiber; Anthony J. Pahl; Michael W. Topping; Naveen A. Reddy; Reinhard Genzel; Sedona H. Price; L. J. Tacconi (The Astrophysical Journal)
We investigate the multiphase structure of gas flows in galaxies. We study 80 galaxies during the epoch of peak star formation (1.4 ≤ z ≤ 2.7) using data from the Keck/Low-Resolution Imaging Spectrometer (LRIS) and the Very Large Telescope/ K -Band Multi-Object Spectrograph (KMOS). Our analysis provides a simultaneous probe of outflows using UV emission and absorption features and H α emission. With this unprecedented data set, we examine the properties of gas flows estimated from LRIS and KMOS in relation to other galaxy properties, such as star formation rate (SFR), SFR surface density (Σ _SFR ), stellar mass ( M _* ), and main-sequence offset (ΔMS). We find no strong correlations between outflow velocity measured from rest-UV line centroids and galaxy properties. However, we find that galaxies with detected outflows show higher averages in SFR, Σ _SFR , and ΔMS than those lacking outflow detections, indicating a connection between outflow and galaxy properties. Furthermore, we find a lower average outflow velocity than previously reported, suggesting greater absorption at the systemic redshift of the galaxy. Finally, we detect outflows in 49% of our LRIS sample and 30% in the KMOS sample and find no significant correlation between outflow detection and inclination. These results may indicate that outflows are not collimated and that H α outflows have a lower covering fraction than low-ionization interstellar absorption lines. Additionally, these tracers may be sensitive to different physical scales of outflow activity. A larger sample size with a wider dynamic range in galaxy properties is needed to further test this picture.